The Evaluation of the Exponential Anomaly as a Consequence of the Doctrine of Modulation of Existence in Education - Muhammad Reza Ershadinia (آموزه‌‌های فلسفه اسلامي)
An article claims by increasing the process of doubting and creating doubt on the ontological principles of Islamic philosophy to have provided innovative flaws on the theory of emanationism, centered on the doctrine of analogical gradation (modulation) in all philosophical schools to show that basing the theory of education on Islamic philosophy is invalid and useless. This article after expressing the scattered words and producing various doubts and choosing the title “Consequences in Education” intends to reach a novel theorizing about the “purpose and stages of education” with the unaccepted obligations of Islamic philosophy! What has been mostly used to criticize the article is a section of the topic of modulation of existence and arguing about some scattered ontological matters, and it has not even mentioned the psychological (self-knowledge) and anthropological positions and the stages of human growth (development) in Islamic philosophy in order to be able to achieve the stages of education in line with the stages of growth in the Islamic philosopher’s perspective and open a seemingly logical way to the audience for doubts. Nevertheless, the article claims to have achieved innovation and rejected two sequencing (Arabic: توالی, succession, consequentialism) and parallelist (Arabic: توازی) theories and has made its way to create a third opinion, which is the combination of both. The analysis of the claims of the article and its accusations against Islamic philosophy, particularly in the field of education will reveal the criterion for distinguishing true criticism from doubting.